The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
Catalysis in Electrochemistry 2011
DOI: 10.1002/9780470929421.ch12
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysis at Liquid–Liquid Interfaces

Abstract: Le transfert assisté de protons utilisant deux porphyrines "base libre" telles que le H 2 TPP et H 2 OEP a été étudié à l'interface eau|1,2-DCE. La formation de di-acid H 4 TPP 2+ et H 4 OEP 2+ , liée à la double protonation de H 2 TPP et H 2 OEP au niveau des nitrogènes tertiaires dans le cycle, a été observée à l'interface par voltamétrie du transfert d'ions ainsi que par spectroscopie en UV visible. De plus, les derivés neutres et ionisées de H 2 TPP ont été déterminés dans le "diagramme de partition ioniqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 253 publications
(212 reference statements)
0
10
0
Order By: Relevance
“…Additionally,t he observed irreversible positive current (Figure 4) rises at Galvani potentials significantly lower than D w DCE 0 0 Hþ (0.58 V). [48] We expect that the interfacial graphene acts as ab ipolar electrode, as suggested previously, [40,42,43] and is therefore doped by electrons from DcMFc in the DCEp hase, which then reduce aqueous oxygen. This n doping is evident from the greater oxidation of DcMFc + observed in the DCEphase stock solution when graphene was present,a sc ompared to the stock solutionc ontaining just DcMFc and the organic supporting electrolyte (Table 1).…”
Section: Decamethylferrocene As the Reducing Agentmentioning
confidence: 64%
See 2 more Smart Citations
“…Additionally,t he observed irreversible positive current (Figure 4) rises at Galvani potentials significantly lower than D w DCE 0 0 Hþ (0.58 V). [48] We expect that the interfacial graphene acts as ab ipolar electrode, as suggested previously, [40,42,43] and is therefore doped by electrons from DcMFc in the DCEp hase, which then reduce aqueous oxygen. This n doping is evident from the greater oxidation of DcMFc + observed in the DCEphase stock solution when graphene was present,a sc ompared to the stock solutionc ontaining just DcMFc and the organic supporting electrolyte (Table 1).…”
Section: Decamethylferrocene As the Reducing Agentmentioning
confidence: 64%
“…[2][3][4] Over the last decade, the use of ITIES systemsf or reduction reactions has received ag reat deal of attention,w ith both the oxygen reduction and hydrogen evolution [28][29][30][31][32][33][34][35][36][37][38] reactions (ORR and HER, respectively) widely studied. [39][40][41] Equations (1)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 This enables a wide range of interfacial processes to be investigated including interfacial assembly and catalytic function. [23][24][25] To this end, protein electrochemistry at the aqueous-organic interface has been studied by many, including reports on the proteins of interest in this work: hemoglobin (Hb), 26, 27 myoglobin (Myo), 28 cytochrome c (Cyt c) 29,30 and lysozyme (Lys). 31 While such studies have led to fine control and understanding of the electrochemical process, there is little information on the influence of the electrochemical interface on the secondary structures of the proteins.…”
Section: Introductionmentioning
confidence: 99%
“…One area of great interest to the ITIES community over the last decade is the study of heterogeneous reduction reactions, primarily the hydrogen evolution and oxygen reduction reactions (HER and ORR, respectively), using lipophilic reducing agents. [24][25][26] Various interfacially adsorbed materials have been used as catalysts for these reactions and the group of Girault found that using MWCNTs 27 and reduced graphene oxide (rGO) 28 as supports for the catalysts Mo 2 C and MoS 2 , respectively, improved the catalytic effect of these materials, compared to their unsupported forms, toward the HER. These effects were attributed to an improved electron transfer from the lipophilic reducing agent to the interfacial catalyst, mediated by the carbon supports.…”
Section: Introductionmentioning
confidence: 99%